THE PEAK APP AS A TOOL IN THE TEACHING AND LEARNING OF STUDENTS WITH ADHD - Carvalho, Márcia Cristina Silva de; Silva, Marcela Gomes da; Silva, Elizabeth Ferreira da; Coutinho, Diogenes José Gusmão (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2024)
By enabling the practical application of knowledge, technology can be used as a mediator in the teaching of students with ADHD. By using digital applications that provide a playful and attractive universe, which increase the ability to concentrate and understand activities, such as the PEAK application. The present study aims to analyze the impacts caused by the use of the PEAK application on the development of learning of students with ADHD. This is a research carried out with a qualitative approach, through the application of a questionnaire as a research mechanism. Despite some limitations, the results obtained show satisfactory levels regarding the use of this application in remote classes.